Digital sovereignty in the Global South: Indonesia’s cyber governance between global power and national autonomy - Pongrekun, Dharma; Sudirman, Arfin; Setiabudi, Widya; Bainus, Arry (Research Journal in Advanced Humanities, 2026)
Indonesia’s national cybersecurity policy is confronting a critical challenge amid an increasingly hegemonic global digital architecture and geopolitical competition. In this context, states are often compelled to adopt international regulatory standards that may undermine national data sovereignty. This article examines how Indonesia can formulate a sovereign cybersecurity policy within an asymmetric global digital governance structure characterized by technological dependency and the dominance of global actors that limit national policy autonomy. Employing a qualitative–interpretive approach with a strategic policy analysis design, the study reveals that global digital governance reproduces structural power asymmetries between advanced economies as technology producers and developing countries as technology consumers and regulatory subjects. These asymmetries facilitate new forms of digital penetration through algorithmic control, infrastructure dependency, and the expanding influence of transnational technology corporations, thereby threatening not only technical security but also data sovereignty and epistemic independence. This article introduces OGDS (One Gate Data System) as an integrated policy framework that synthesizes governance, resilience, ethics, and diplomacy. By reframing digital self-reliance as a political and normative project, OGDS positions Indonesia not merely as a passive adopter of global standards but as a potential architect of a sovereign and ethical digital order grounded in the values of Pancasila.